Problem dopuszczalności stosowania przemocy w obronie zwierząt w teorii praw zwierząt Toma Regana - Gzyra, Dariusz (Zoophilologica. Polish Journal of Animal Studies, 2015)
The article analyzes the position of Tom Regan (the author of a theory of animal rights) toward the admissibility of the use of force in defense of animals. The key issue here is the definitional dispute about the legitimacy of violent actions directed towards things and defining the criteria that justify such violence. Regan’s conclusion is presented in the context of different forms of violence as well as its definition, the contemporary realities of animal exploitation, and the history of direct action in defense of animals.